2015
DOI: 10.1007/s10815-015-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of single-nucleotide polymorphisms rs2197076 and rs2241883 of FABP1 gene with polycystic ovary syndrome

Abstract: In the association of SNPs in FABP1 gene with PCOS, rs2197076 was more closely associated with its main features than rs2241883 and seemed to play a more important role in the pathogenesis of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Regarding the FABP1 gene, Xue et al investigated the relationship between SNP rs2197076 and rs2241883 and PCOS. In their study of 221 PCOS women and 198 normal women, the authors found a close association with rs 2197076 and rs 2241883 polymorphisms in women with PCOS but no association with BMI [19]. In a study of 95 PCOS women and 45 healthy women, Rashid et al found that the allele and genotype frequency of IL-1β, IL-1Ra, and FABP1 gene polymorphisms did not differ between the PCOS and control groups.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the FABP1 gene, Xue et al investigated the relationship between SNP rs2197076 and rs2241883 and PCOS. In their study of 221 PCOS women and 198 normal women, the authors found a close association with rs 2197076 and rs 2241883 polymorphisms in women with PCOS but no association with BMI [19]. In a study of 95 PCOS women and 45 healthy women, Rashid et al found that the allele and genotype frequency of IL-1β, IL-1Ra, and FABP1 gene polymorphisms did not differ between the PCOS and control groups.…”
Section: Discussionmentioning
confidence: 93%
“…Secondly, environmental factors might also influence the relationship between TNF-α/IL-1/IL-6/IL-10 polymorphisms and PCOS. However, most investigators only focused on genetic associations in their works, and so the geneticenvironmental interactions were not explored in this meta-analysis [21]. Thirdly, we did not consider grey literature.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic differentiation although low in absolute Fst values should be taken into account during association studies. We identified 10 medically relevant SNVs with statistically significant allele differences between the NVSB and NFE populations including rs2241883 in FABP1 gene previously associated with polycystic syndrome [21] and toxicity of fenofibrate [22], rs1801274 variant in FCGR2A gene shown to be important for the efficiency of trastuzumab in breast neoplasms [23], the rare rs17879961 variant in CHEK2 gene reliably associated with predisposition to breast and colorectal cancer [24] and showed elevated frequency in NVSB. These variants should be studied in future on an expanded dataset with associated clinical data.…”
Section: Discussionmentioning
confidence: 99%